The balancing act between skiing and shooting - the determinants of success in biathlon pursuit and mass start events - Björklund, G.; Dzhilkibaeva, N.; Gallagher, C.; Laaksonen, M. S. (Journal of Sports Sciences, 2022)
This study aimed to investigate how skiing speed (SS), number of missed targets (MT) and range time (RT) were associated with final rank in biathlon pursuit and mass start competitions. Data were collected from the International Biathlon Union`s database over 17 seasons. Biathletes were categorised into three groups (rank 1-3, G3; rank 4-10, G10; rank 11-20, G20). Multinomial regression was used to identify odds ratios associated with group rank in both sexes. The only variable found to be consistently related to G3 in both pursuit and mass start was MT (men OR 1.206-1.729 and women OR 1.340-3.124, all p < 0.01). SS during lap four of pursuit and mass start was most strongly related to G3 for both sexes (men OR 0.231-0.094 and women OR 0.339-0.126, all p < 0.001). RT during shooting four in pursuit was most strongly related to G3 compared to G10 and G20 (men OR 1.067; 95% CI, 1.030-1.105 and women OR 1.076; 95% CI, 1.020-1.134, all p < 0.001, respectively). Accordingly, MT was most strongly related to final rank in both sexes, while SS during lap four and last RT was also significant.